Nonsurgical treatment of an extensive radiolucent lesion, a case report - Moshari, Amirabbas; Vatanpour, Mehdi; EsnaAshari, Ehsan; Zakershahrak, Mehrsa; Jalali Ara, Afsoon (Iranian Endodontic Journal, 2016)
Long-term success of endodontic treatment is precisely and completely dependent on adequate and appropriate cleaning and shaping of the root canal along with proper and correct obturation of the entire prepared space. This paper aims to report an exceptionally and novel non-surgical and orthograde endodontic therapy on maxillary right central incisor with an extensive radiolucent lesion. A 17-year-old male with an unusual extensive radiolucent lesion in the anterior part of upper jaw is reported. After cleaning and shaping of the root canal, Calcium Hydroxide was placed in the canal for 6 months and then Obturation was performed. 6 and 20 months follow-ups showed significant changes, including bone formation and periapical healing at the site of the lesion. The patient was asymptomatic. After 20 months, complete radiographic and clinical healing of the periapical lesion was observed.